2023
DOI: 10.1021/acsami.3c03952
|View full text |Cite
|
Sign up to set email alerts
|

Surface Decorations on Mixed Ionic and Electronic Conductors: Effects on Surface Potential, Defects, and the Oxygen Exchange Kinetics

Abstract: The oxygen exchange kinetics of epitaxial Pr 0.1 Ce 0.9 O 2−δ electrodes was modified by decoration with submonolayer amounts of different basic (SrO, CaO) and acidic (SnO 2 , TiO 2 ) binary oxides. The oxygen exchange reaction (OER) rate and the total conductivity were measured by in situ PLD impedance spectroscopy (i-PLD), which allows to directly track changes of electrochemical properties after each deposited pulse of surface decoration. The surface chemistry of the electrodes was investigated by near-ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 66 publications
2
12
1
Order By: Relevance
“…Possibilities to alter the equilibrium reaction rate include lowering the activation barrier of the rate limiting step, changing participating defect concentrations and altering the energetics of reaction steps before the rate limiting step 23 . Considering that several previous studies have shown that surface decorations do not alter the activation energy of the oxygen exchange reaction substantially 9,14,23,[25][26][27][28] , it is unlikely that a lowered activation barrier of the rate limiting step is the primary cause for increased reaction rates. Instead, we suspect that surface decorations affects both, energetics of adsorbates on the decorated surfaces, as well as charge carrier concentrations.…”
Section: Oxygen Exchange Kinetics Modified By Surface Decorationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Possibilities to alter the equilibrium reaction rate include lowering the activation barrier of the rate limiting step, changing participating defect concentrations and altering the energetics of reaction steps before the rate limiting step 23 . Considering that several previous studies have shown that surface decorations do not alter the activation energy of the oxygen exchange reaction substantially 9,14,23,[25][26][27][28] , it is unlikely that a lowered activation barrier of the rate limiting step is the primary cause for increased reaction rates. Instead, we suspect that surface decorations affects both, energetics of adsorbates on the decorated surfaces, as well as charge carrier concentrations.…”
Section: Oxygen Exchange Kinetics Modified By Surface Decorationsmentioning
confidence: 98%
“…While previous studies have used the Smith acidity of the decoration as a descriptor to predict these changes 9,13,14 , we introduce the ionic potential of surface cations as an alternative metric to describe surface acidity. Based on the definition by Cartledge 15 , we define the surface ionic potential φ as the ratio of ionic charge q and ionic radius r, averaged over the surface cation stoichiometry (with cation fractions x i )…”
Section: Tuning the Work Function With Ultra-thin Oxide Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…4–7 In two recent studies, it has been shown that surface modifications have a huge role in controlling oxygen exchange kinetics in Pr-doped ceria, and that their effect can be correlated with their acidity. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…To address the above issues, there are two feasible approaches: (I) adjusting the electronic structure of cobalt pentlandite to optimize the interaction between catalytic sites and oxygen-containing intermediates; (II) modifying the surface of cobalt pentlandite catalysts to increase the number of active sites. , On the one hand, the direct use of high-valence metal cations doping such as V 3+ , W 6+ , and Mo 6+ ions have been proven to adjust the local coordination environment electronic structure, and accelerate electron transfer kinetics, leading to an optimized OER catalytic activity . Li et al designed and synthesized a novel Vanadium­(V) doped NiFe LDH, which exhibited excellent catalytic activity.…”
Section: Introductionmentioning
confidence: 99%